Preparation method of negative optical filter
By plating Ta2O5 and SiO2 film systems with specific hierarchical structures on the lens, combined with vacuum coating and radio frequency ion source technology, negative filters with excellent performance were prepared, which solved the problem of poor transmittance and barrier effects of existing filters in a specific wavelength range, and achieved the effect of high transmittance and barriers at a specific wavelength, and was suitable for eye protection and other applications.
Patent Information
- Application Number
- CN202411617326.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
AI Technical Summary
The transmittance and barrier effects of existing negative filters in a specific wavelength range are not ideal, and it is difficult to meet the demand for high transmittance and barriers for specific wavelengths in certain application fields.
A negative filter preparation method is adopted to optimize coating parameters to improve transmission and barrier effects by plating 34 layers of Ta2O5 and SiO2 on the first side of the lens and 4 layers of Ta2O5 and SiO2 on the second side.
It has achieved an average transmittance value of more than 96% in the 380-405nm band, an average transmittance value of more than 98% in the 485-545nm band, and a transmittance value of less than 0.1% in the 435-465nm band. It is suitable for filtering blue light bands with strong phototoxicity and is suitable for eye protection and other applications.
Smart Images

Figure CN119530718A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of optical filters, and more specifically to a method for preparing a negative optical filter. Background Art
[0002] The main function of a negative filter is to transmit most wavelengths and only attenuate the light within a specific wavelength range (also called stop band) to a very low level (a very low level, not completely cut off).
[0003] In the medical, scientific, and industrial fields, negative filters can effectively attenuate excitation light or stray light, thereby protecting workers. They can also improve the signal-to-background ratio, enhance image quality, and measurement accuracy.
[0004] In some Raman applications, negative filters can be used to block the excitation wavelength while transmitting the Stokes and anti-Stokes signals to the detector. For example, in Raman spectroscopy experiments, in order to obtain a better signal-to-noise ratio, the pump laser can be suppressed by placing a negative filter in the detection channel. In addition to spectrometers, negative filters are also frequently used in laser-based fluorescence instrumentation and biomedical laser systems. Like all dielectric stack filters, the transmission of negative filters is incident angle dependent. The center wavelength of the stopband region shifts to shorter wavelengths as the angle of incidence increases.
[0005] Negative filters are widely used in the following fields: Optical field: Negative filters play an important role in optical instruments, lasers, fiber-optic communications, optical measurements and other fields; Electronic field: Negative filters are also widely used in spectrum analysis, signal processing, radio, radar and other fields; Biomedical field: Negative filters play an important role in biomedical imaging and analysis, and can be used in fluorescence microscopy, fluorescence probes and other aspects; Astronomy field: In astronomical observations, negative filters are used to screen specific wavelength ranges to isolate signals of interest.
[0006] Therefore, the development of negative filters for specific wavelength ranges needs to be further developed to improve performance. Summary of the invention
[0007] In view of the problems existing in the background technology, an object of the present invention is to provide a method for preparing a negative filter, wherein the prepared negative filter has an average transmittance of more than 96% in the 380-405nm band from ultraviolet light to visible light at a test angle of 0°, an average transmittance of more than 98% in the 485-545nm band, and an average transmittance of less than 0.1% in the cutoff band of 435-465nm.
[0008] Thus, a method for preparing a negative filter comprises the following steps: S1, cleaning the surface of a glass substrate product as a lens; S2, placing the treated lens into a fixture, and hanging the mounted lens into a vacuum coating machine cavity, wherein the temperature of the cavity is set to 160°C; S3, starting the vacuum coating machine to evacuate the vacuum to a degree of vacuum of 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 8min, the parameters of the RF ion source are: output ion acceleration voltage 850V, output ion current 850mA, grid ion deflection voltage 700V, argon flow rate 10sccm, oxygen flow rate 70sccm; S4, coat the IR film system on the first side of the lens, the IR film system is: Sub / 7.74H357.73L 7.69H 339.55L22.12H 339.4L 23.94H 322.79L 34.83H285.18L 80.95H 267.65L 44.81H 297.64L60.99H 280.93L 51.71H293.82L 53.75H 282.06L 61.19H 274.21L 70.02H 277.82L43.67H300.08L 61.57H 291L 27.94H 328.78L 38.29H 326.7L 14.82H405.54L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness of Ta 2 O 5 film layer, L represents a λ 0 / 4 optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2 The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film layer is 0.8nm / s; S5, after the IR film system is coated on the first side of the lens, wait for the chamber to cool to below 60-70°C and take out the fixture together with the product; S6, repeat steps S1 to S3; S7, coat the AR film system on the second side of the lens, the AR film system is Sub / / 11.57H 28.92L 102.9H74.38L / Air, where Sub is the glass substrate, Air is air, and H represents a λ 0 / 4 Optical thickness of Ta 2 O5 film layer, L represents a λ 0 / 4 optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2 The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film layer is 0.8nm / s; S8, after the AR film system is coated on the second side of the lens, wait for the cavity to cool down to below 60-70°C and take out the fixture together with the product.
[0009] The beneficial effects of the present disclosure are as follows.
[0010] In the preparation method of the negative filter according to the present disclosure, Ta is plated on the first surface of the lens. 2 O 5 and SiO 2 Step S4 of the IR film system composed of 34 layers and coating Ta on the second surface of the lens 2 O 5 and SiO 2 In step S7 of the AR film system composed of 4 layers, combined with the surface cleaning of steps S1 and S6, the chamber temperature of steps S2 and S6, the ion source cleaning of steps S3 and S6, and the cooling of steps S5 and S8, as verified by Example 1 of the test process described later, the test angle is 0° from the ultraviolet light band to the visible light band, the average transmittance in the 380-405nm band (ultraviolet band) is greater than 96%, the average transmittance in the 485-545nm band (visible light band) is greater than 98%, and the average transmittance in the cut-off band 435-465nm band is less than 0.1%.
[0011] The negative filter prepared according to the preparation method of the negative filter disclosed in the present invention is very suitable for filtering the 435-465nm band (i.e. the blue light band with strong phototoxicity), and is therefore very suitable for eye protection of various display screens such as laptops, computers, and smart phones. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a curve diagram of the transmittance from the ultraviolet light band to the visible light band at a test angle of 0° in Example 1. DETAILED DESCRIPTION
[0013] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0014] [Method for preparing negative filter]
[0015] The method for preparing the negative filter according to the present disclosure comprises the steps of:
[0016] S1, cleaning the surface of a product serving as a glass substrate of a lens;
[0017] S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 160℃;
[0018] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 8min, the parameters of the RF ion source are: exit ion acceleration voltage 850V, exit ion current 850mA, grid ion deflection voltage 700V, argon flow rate 10sccm, oxygen flow rate 70sccm;
[0019] S4, IR (Infrared) coating is applied on the first side of the lens, IR coating is: Sub / 7.74H357.73L 7.69H339.55L 22.12H 339.4L 23.94H 322.79L 34.83H285.18L 80.95H 267.65L 44.81H297.64L 60.99H 280.93L 51.71H293.82L 53.75H 282.06L 61.19H 274.21L 70.02H277.82L 43.67H300.08L 61.57H 291L 27.94H 328.78L 38.29H 326.7L 14.82H405.54L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness of Ta 2 O 5 film layer, L represents a λ 0 / 4 optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film layer is 0.8nm / s;
[0020] S5, after the IR coating system is applied to the first side of the lens, wait for the cavity to cool down to below 60-70°C and take out the fixture together with the product;
[0021] S6, repeating steps S1 to S3;
[0022] S7, AR (Anti-Reflection) coating is applied on the second side of the lens. The AR coating is Sub / / 11.57H28.92L 102.9H 74.38L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness of Ta 2 O 5 film layer, L represents a λ 0 / 4 Optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2 The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film layer is 0.8nm / s;
[0023] S8, after the AR coating system is coated on the second side of the lens, wait for the cavity to cool down to below 60-70℃ and then take out the fixture together with the product.
[0024] In the preparation method of the negative filter according to the present disclosure, Ta is plated on the first surface of the lens. 2 O 5 and SiO 2 Step S4 of the IR film system composed of 34 layers and coating Ta on the second surface of the lens 2 O 5 and SiO 2In step S7 of the AR film system composed of 4 layers, combined with the surface cleaning of steps S1 and S6, the chamber temperature of steps S2 and S6, the ion source cleaning of steps S3 and S6, and the cooling of steps S5 and S8, as verified by Example 1 of the test process described later, the test angle is 0° from the ultraviolet light band to the visible light band, the average transmittance in the 380-405nm band (ultraviolet band) is greater than 96%, the average transmittance in the 485-545nm band (visible light band) is greater than 98%, and the average transmittance in the cut-off band 435-465nm band is less than 0.1%.
[0025] The negative filter prepared according to the preparation method of the negative filter disclosed in the present invention is very suitable for filtering the 435-465nm band (i.e. the blue light band with strong phototoxicity), and is therefore very suitable for eye protection of various display screens such as laptops, computers, and smart phones.
[0026] The surface cleaning in step S1 and step S6 is beneficial to improving the surface state of the first surface and the second surface of the lens, and is helpful to improve the bonding performance of the IR film system on the first surface and the AR film system on the second surface with the corresponding surface of the lens. For example, the surface of the lens is cleaned by ultrasonic wave or hand rubbing. Further, in step S1, the surface cleaning of the lens by ultrasonic wave is polished by aluminum oxide polishing liquid, and then ultrasonic pure water cleaning. For example, the aluminum oxide polishing liquid adopts the 0.1μm polycrystalline diamond liquid of Nanjing Henry Precision Optics Co., Ltd.
[0027] In one example, in step S1, the glass substrate is K9 glass. For example, in step S1, the thickness of the glass substrate is 1 mm.
[0028] The temperature setting of step S2 heats the lens through the cavity of the coating machine, which helps Ta 2 O 5 The film grows from the lens and reduces Ta 2 O 5 Growth stress. The vacuum coating machine in step S2 is, for example, an Opto-Tech OTFC-1300 with a radio frequency ion source produced by Opto-Tech (Shanghai) Co., Ltd.
[0029] Step S3 uses a radio frequency ion source to clean the surface of each surface of the lens, removing impurities and oil molecules adsorbed on the surface, thereby greatly improving the interface state and helping Ta 2 O 5 The combination of the film layer and the lens is improved. At the same time, the RF ion source is used for cleaning, which can heat all sides of the lens and help Ta 2 O 5 The film grows from the lens and reduces Ta 2 O 5Film growth stress.
[0030] In one example, in step S4 and step S7, Ta is plated 2 O 5 The parameters of the RF ion source used in the film layer are: ion acceleration voltage 1150V, ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm; SiO 2 The parameters of the RF ion source used in the film layer are: exit ion acceleration voltage 900V, exit ion current 900mA, grid ion deflection voltage 600V, argon flow rate 8sccm, and oxygen flow rate 50sccm.
[0031] [test]
[0032] Example 1
[0033] The preparation method of the negative filter of Example 1 adopts the following steps:
[0034] S1, using ultrasonic cleaning to clean the surface of a glass substrate of a lens, the glass substrate is K9 glass, the thickness of the glass substrate is 1 mm, and the surface cleaning of the lens by ultrasonic cleaning is polishing with aluminum oxide polishing liquid, followed by ultrasonic pure water cleaning, the aluminum oxide polishing liquid is a 0.1 μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.;
[0035] S2, putting the processed lens into the fixture, and hanging the mounted lens into the cavity of the vacuum coating machine. The temperature of the cavity is set to 160°C. The vacuum coating machine is the Opto-Tech OTFC-1300 with a radio frequency ion source produced by Opto-Tech (Shanghai) Co., Ltd.;
[0036] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 8min, the parameters of the RF ion source are: exit ion acceleration voltage 850V, exit ion current 850mA, grid ion deflection voltage 700V, argon flow rate 10sccm, oxygen flow rate 70sccm;
[0037] S4, IR coating is applied on the first side of the lens, IR coating is: Sub / 7.74H 357.73L7.69H 339.55L22.12H 339.4L 23.94H 322.79L 34.83H 285.18L80.95H 267.65L 44.81H 297.64L60.99H 280.93L 51.71H 293.82L53.75H 282.06L 61.19H 274.21L 70.02H 277.82L43.67H 300.08L61.57H 291L 27.94H 328.78L 38.29H 326.7L 14.82H 405.54L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness of Ta 2 O 5 film layer, L represents a λ 0 / 4 optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2 The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film layer is 0.8nm / s;
[0038] S5, after the IR coating system is applied to the first surface of the lens, the fixture and the product are taken out after the cavity is cooled to 65°C;
[0039] S6, repeating steps S1 to S3;
[0040] S7, AR coating is applied on the second side of the lens. The AR coating is Sub / / 11.57H 28.92L102.9H 74.38L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness of Ta 2 O 5 film layer, L represents a λ 0 / 4 Optical thickness SiO 2 Film layer, λ 0 is the wavelength of incident light, the number before H and L is the thickness of the film in nm, Ta 2 O 5 and SiO 2The film layers are all deposited by electron beam evaporation and assisted by radio frequency ion source. 2 O 5 The deposition rate of the film is 0.3nm / s, SiO 2 The deposition rate of the film is 0.8nm / s;
[0041] S8, after the AR coating system is coated on the second side of the lens, wait for the cavity to cool to 65°C and take out the fixture together with the product;
[0042] In step S4 and step S7, Ta is plated 2 O 5 The parameters of the RF ion source used in the film layer are: ion acceleration voltage 1150V, ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm; SiO 2 The parameters of the RF ion source used in the film layer are: exit ion acceleration voltage 900V, exit ion current 900mA, grid ion deflection voltage 600V, argon flow rate 8sccm, and oxygen flow rate 50sccm.
[0043] Figure 1 It is a curve diagram of the transmittance from the ultraviolet light band to the visible light band at a test angle of 0° in Example 1.
[0044] from Figure 1 It can be seen that from the ultraviolet light band to the visible light band with a test angle of 0°: the average transmittance in the 380-405nm band (ultraviolet band) is greater than 96%, the average transmittance in the 485-545nm band (visible light band) is greater than 98%, and the average transmittance in the cutoff band 435-465nm is less than 0.1%.
[0045] The overall performance of the product and the film systems on both sides are tested as follows.
[0046] Water bubble test: The product prepared in Example 1 together with the IR film system on the first surface and the AR film system on the second surface were subjected to a water bubble test with tap water for 10 minutes. It was found that the IR film system on the first surface and the AR film system on the second surface did not fall off the product, and there was no cracking of the IR film system on the first surface and the AR film system on the second surface.
[0047] Adhesion test: After the bubble test with tap water was completed, the IR film system on the first side of the product pasted with 3M tape was pulled by hand in the direction opposite to the pasting end, and the IR film system was not pulled up; for the second side of the product, the AR film system on the second side of the product pasted with 3M tape was pulled by hand in the direction opposite to the pasting end, and the AR film system was not pulled up.
[0048] The water bubble test and adhesion test show that the IR film on the first side and the AR film on the second side of the product have good adhesion.
[0049] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a negative filter, characterized in that: Includes steps: S1, cleaning the surface of a product serving as a glass substrate of a lens; S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 160℃; S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 8min, the parameters of the RF ion source are: exit ion acceleration voltage 850V, exit ion current 850mA, grid ion deflection voltage 700V, argon flow rate 10sccm, oxygen flow rate 70sccm; S4, IR coating is applied on the first side of the lens, IR coating is: Sub / 7.74H 357.73L7.69H 339.55L22.12H 339.4L 23.94H 322.79L 34.83H 285.18L80.95H 267.65L 44.81H 297.64L60.99H 280.93L 51.71H 293.82L53.75H 282.06L 61.19H 274.21L 70.02H 277.82L43.67H 300.08L61.57H 291L 27.94H 328.78L 38.29H 326.7L 14.82H 405.54L / Air, where Sub is the glass substrate, Air is air, H represents a Ta2O5 film with an optical thickness of λ0 / 4, L represents a SiO2 film with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, and the numbers before H and L are the thickness of the film in nm. Both Ta2O5 and SiO2 films are deposited by electron beam evaporation and assisted by radio frequency ion source evaporation. The deposition rate of Ta2O5 film is 0.3nm / s, and the deposition rate of SiO2 film is 0.8nm / s. S5, after the IR coating system is applied to the first side of the lens, wait for the cavity to cool down to below 60-70°C and take out the fixture together with the product; S6, repeating steps S1 to S3; S7, AR coating is applied on the second side of the lens. The AR coating is Sub / / 11.57H 28.92L102.9H 74.38L / Air, where Sub is the glass substrate, Air is air, and H represents a lambda 0 / 4 optical thickness Ta2O5 film, L represents a λ0 / 4 optical thickness SiO2 film, λ0 is the wavelength of incident light, the numbers before H and L are the thickness of the film in nm, Ta2O5 and SiO2 films are both deposited by electron beam evaporation and assisted by radio frequency ion source, the deposition rate of Ta2O5 film is 0.3nm / s, and the deposition rate of SiO2 film is 0.8nm / s; S8, after the AR coating system is coated on the second side of the lens, wait for the cavity to cool down to below 60-70℃ and then take out the fixture together with the product.
2. The method for preparing a negative filter according to claim 1, characterized in that: In step S1, the surface of the lens is cleaned by ultrasonic wave or hand wiping.
3. The method for preparing a negative filter according to claim 2, characterized in that: In step S1, the surface of the lens is cleaned by using ultrasonic waves, which includes polishing with aluminum oxide polishing liquid and then ultrasonic pure water cleaning; The alumina polishing liquid adopts the 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
4. The method for preparing a negative filter according to claim 1, characterized in that: In step S1 , the glass substrate is K9 glass.
5. The method for preparing a negative filter according to claim 1, characterized in that: In step S1 , the thickness of the glass substrate is 1 mm.
6. The method for preparing a negative filter according to claim 1, characterized in that: In step S2, the vacuum coating machine is an OTFC-1300 vacuum coating machine.
7. The method for preparing a negative filter according to claim 1, characterized in that: In step S4 and step S7, The parameters of the radio frequency ion source used for coating the Ta2O5 film are: output ion acceleration voltage 1150V, output ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm; The parameters of the radio frequency ion source used in the deposition of the SiO2 film are: exit ion acceleration voltage 900 V, exit ion current 900 mA, grid ion deflection voltage 600 V, argon flow rate 8 sccm, oxygen flow rate 50 sccm.
Citation Information
Cited By
Preparation method of stray light-resistant high-transmittance coated lens
CN121380842A
Method for preparing anti-stray light high-transmission coated lenses
CN121380842B